2019
DOI: 10.1001/jamanetworkopen.2019.15717
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Views of Research Participant Willingness to Participate and Share Digital Data in Biomedical Research

Abstract: Key PointsQuestionAre people willing to participate in research advertised on the internet, and is willingness to participate associated with type of study sponsor?FindingsThis mixed-methods survey and qualitative study of 914 respondents indicated that they were more likely to participate and share their social media data with researchers in university-led research studies than in studies conducted by the US federal government or pharmaceutical companies. However, only 49.3% indicated they would share their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
(33 reference statements)
2
38
1
Order By: Relevance
“…However, further research is needed to identify whether and how views on ethical concerns differed between social media platforms and across populations. • Two studies analysed the ethical concerns related to recruitment [6,8]. First study was selected as best paper [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, further research is needed to identify whether and how views on ethical concerns differed between social media platforms and across populations. • Two studies analysed the ethical concerns related to recruitment [6,8]. First study was selected as best paper [6].…”
Section: Discussionmentioning
confidence: 99%
“…The expressed attitudes were highly contextual, depending on factors such as the type of disease or health topic and the entity or person who monitored users on Twitter. In the second paper [8], authors tried to determine whether willingness to participate and willingness to share social media data are associated with the type of research team and online recruitment platform. Participants were significantly less likely to participate in federally sponsored or pharmaceutical company research than university-led studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Practically speaking, it is nearly impossible to guarantee anonymity, in that when more data about an individual becomes available it might reveal patterns of behavior or characteristics that could reveal the individual's identity. Research has shown that the willingness to participate in biomedical research advertised on social media platforms and search engines, as well as the willingness to share digital data with researchers, have been affected by recent news on the misuse of such data [39]. However, research about willingness to share data in health social media is still in its infancy and hence, further research in this space within a participatory health paradigm is warranted [40].…”
Section: Data Privacy Security and Quality Assurance Are The Most Rmentioning
confidence: 99%